A new STI in the city: MPOX in Barcelona. First outbreak (5/2022-5/2023) and subsequent resurgence. - David Palma; Montserrat Guillaumes; Carles Pericas; Anna de Andrés; Raquel Prieto; Laia Álvarez-Bruned; Jesús Ospina; Paula Santiá; Patricia García de Olalla; Cristina Rius (PLoS ONE)
Background In May 2022, after the suspension of the mobility restrictions due to the COVID-19 pandemic, the first outbreak of MPOX virus, transmitted from human to human, was detected outside of Africa, affecting mostly sexually active men who have sex with men. Our aim is to report the first outbreak of MPOX in Barcelona city in the period from 5/2022 to 5/2023 and the subsequent surge of cases in 8/2023. Methods We performed a descriptive study of all notified cases in city residents, obtained through epidemiological surveys. The analyses are presented for the hospitalized cases and the key population of men who have sex with men. Results Of 2037 notified cases, 82.6% were confirmed. The cumulative incidence in the general population was 1.03 (95%CI 1.00-1.06) per 1000 inhabitants and 2.13 (2.01-2.17) per 1000 in men. Men were older than women, with a median age of 37 years (interquartile range 31-43). While 84.5% of men reported having sex with partners of the same gender, 70.9% of women only reported sex with partners of the opposite gender. Complications occurred in 4.1% of infected persons, 1.6% required hospitalization, and no deaths were registered. Georeferencing was highly associated with gay venues. Gay, bisexual and other men who have sex with men (GBMSM) accounted for most cases and severe cases, and were associated with attending public sex venues and not providing contact tracing information. Digital and printed prevention campaign materials were developed for GBMSM. Discussion The 2022 MPOX outbreak posed a major challenge to surveillance and sexual health services worldwide. With new cases and re-infections on the rise, MPOX may become a regular infection to be incorporated in STI testing and management guidelines. Barcelona has some characteristics that may facilitate the occurrence and spread of emergencies related to sexual health.